2023
DOI: 10.3390/nano13081419
|View full text |Cite
|
Sign up to set email alerts
|

UV-Excited Luminescence in Porous Organosilica Films with Various Organic Components

Abstract: UV-induced photoluminescence of organosilica films with ethylene and benzene bridging groups in their matrix and terminal methyl groups on the pore wall surface was studied to reveal optically active defects and understand their origin and nature. The careful selection of the film’s precursors and conditions of deposition and curing and analysis of chemical and structural properties led to the conclusion that luminescence sources are not associated with the presence of oxygen-deficient centers, as in the case … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 73 publications
2
3
0
Order By: Relevance
“…Figure 11 demonstrates the dependence of the photoluminescence intensity on the wavelength of the excited light. The highest PL intensity is observed when the excitation wavelength is 230 nm, which aligns with previously reported data [34].…”
Section: Uv-induced Luminescencesupporting
confidence: 92%
See 2 more Smart Citations
“…Figure 11 demonstrates the dependence of the photoluminescence intensity on the wavelength of the excited light. The highest PL intensity is observed when the excitation wavelength is 230 nm, which aligns with previously reported data [34].…”
Section: Uv-induced Luminescencesupporting
confidence: 92%
“…Figure 11 demonstrates the dependence of the photoluminescence intensity on the wavelength of the excited light. The highest PL intensity is observed when the excitation wavelength is 230 nm, which aligns with previously reported data [34]. Practical fluorescence quenching, caused by the aggregation of Eu 3+ , becomes evident in silica glass when the Eu content exceeds 1% (molar ratio) [45].…”
Section: Uv-induced Luminescencesupporting
confidence: 91%
See 1 more Smart Citation
“…The photoluminescent materials investigated include crystalline tris(8-hydroxyquinoline) aluminum (Alq3) micro-rods (MRs), Fe 2+ -doped CsPb(Cl x Br 1−x ) 3 nanocrystals (NCs), organosilica films, and Tm 3+ -doped SiO 2 –HfO 2 [ 4 , 5 , 6 , 7 ]. Kim et al fabricated hybrid Alq3/Ag structures using a self-assembly method under a mixed solution of protic and aprotic polar solvents [ 4 ].…”
mentioning
confidence: 99%
“…They showed that the PL intensity could be improved by increasing the porosity and internal surface area. Wu et al prepared Fe 2+ -doped CsPb(Cl x Br 1−x ) 3 NCs using a hot injection method [ 6 ]. Since the defect density was reduced by the Fe 2+ doping, the full width at half maximums declined, while PL quantum yields (QYs) and photostability increased.…”
mentioning
confidence: 99%